2017
DOI: 10.1016/s1470-2045(16)30570-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrating primary care providers in the care of cancer survivors: gaps in evidence and future opportunities

Abstract: For over a decade since the release of the Institute of Medicine report, From Cancer Patient to Cancer Survivor: Lost in Transition, there has been a focus on providing coordinated, comprehensive care for cancer survivors that emphasized the role of primary care. Several models of care have been described which primarily focused on primary care providers (PCPs) as receivers of cancer survivors and specific types of information (e.g. survivorship care plans) from oncology based care, and not as active members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
184
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(190 citation statements)
references
References 57 publications
3
184
0
3
Order By: Relevance
“…Even among CHC patients who can access care regardless of insurance status, patients appear to be less likely to receive preventive care while uninsured. In integrated health care settings and pilot studies, EHRs have facilitated the coordination and transition of care between oncologists and PCPs, 9,46 but little evidence of this process has been documented in other settings, such as CHCs, or across different EHR systems. 43 Survivorship care plans may help to bridge gaps in care during the transition from oncology to primary care, 2,44 and feasibly could be exchanged across EHRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even among CHC patients who can access care regardless of insurance status, patients appear to be less likely to receive preventive care while uninsured. In integrated health care settings and pilot studies, EHRs have facilitated the coordination and transition of care between oncologists and PCPs, 9,46 but little evidence of this process has been documented in other settings, such as CHCs, or across different EHR systems. 43 Survivorship care plans may help to bridge gaps in care during the transition from oncology to primary care, 2,44 and feasibly could be exchanged across EHRs.…”
Section: Discussionmentioning
confidence: 99%
“…43 Survivorship care plans may help to bridge gaps in care during the transition from oncology to primary care, 2,44 and feasibly could be exchanged across EHRs. 46 The development of standard flowsheets or templates for survivorship care plans in EHRs may facilitate the systematic study of these plans and address the lack of definitive data demonstrating the benefits to patients of these widely encouraged tools. In integrated health care settings and pilot studies, EHRs have facilitated the coordination and transition of care between oncologists and PCPs, 9,46 but little evidence of this process has been documented in other settings, such as CHCs, or across different EHR systems.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer survivors are vulnerable to suffering from second cancer and comorbid chronic conditions with advanced age [34]. Historically, most cancer patients were followed up by hospital specialists [56]. However, Nielsen et al [7] believes that most cancer patient might feel left alone after they are discharged from the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…A second review [18] argued that local health care practitioners could benefit patients with physical and psychosocial problem in survivorship care, but proactive initiatives should be conducted to involve PDPs in the follow-up. However, although integrating PCPs into the survivorship care is needed, recent reviews found little evidence regarding the effectiveness of shared care, and there is a lack of standard models of shared care [6101419]. …”
Section: Introductionmentioning
confidence: 99%
“… Expert consensus and modeling are needed to determine how to classify the personalized care needs of patients. Integrating across available models from the literature and the UK modeling of patient categorization yields a starting point for developing a candidate stratified care model that categorizes the types of patients and appropriate pathways of follow‐up care based on the type(s) and level(s) of resources needed for their long‐term care (see Table ). To improve patient outcomes and downstream health care utilization, US models for follow‐up care may follow the UK process and focus on chronic disease management, where the basis of care across care pathways is supporting patients in self‐managing their symptoms and follow‐up care needs while identifying those patients who need more medical intervention. Communication between oncology, primary care, and specialty care providers and communication with patients are essential for delivering personalized follow‐up care pathways.…”
Section: Developing a Blueprint For Implementation In The United Statesmentioning
confidence: 99%